The Analysis of the Visual Image: Historical Approach from the Teaching of the Plastic Arts - Prado Soriano, Leandro Ernesto; Nowak, Joachim; Konova, Andrea; Hubková, Svetlana (Journal of Education Culture and Society, 2024)
Aim. In the article, a historical approach to the analysis of the visual image is made in the way in which the didactic studies applied to the plastic arts in Latin America have treated it, with emphasis on Cuba, Spain, Brazil and Argentina. Methods. The methods used are historical-logical and document analysis. Results. As a result, a historical-trend study of the analysis of the visual image is offered during the last three centuries, a period in which it is possible to speak of a thought and didactic related to the plastic arts in the region. Conclusion. The trend historical study and the criticism carried out demonstrate the need to base a method of analysis of the visual image that really responds to the purpose and objectives of Primary Education. Cognitive value. The analysis of the visual image is an essential component of the didactics of plastic education that requires a renewal based on the knowledge of its historical evolution and the contributions of science on art.